Analisis Nilai-Nilai Kepemimpinan Residen Mohamad Mangoendiprojo Sebagai Pembelajaran Bagi Kaum Milenial Pada Mata Pelajaran Sejarah Di SMA Negeri 1 Terbanggi Besar T.A 2020/2021 - Achmad Didik Khoirudin; Warto Warto; Suryo Ediono; Muadz Assidiqi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Leadership is an attitude that should be owned by everyone, including students. Being a leader is certainly not an easy thing to learn. Learning must be a vehicle for the development of students' potentials not only cognitively but also effectively as well as leadership. History learning is one of the subjects that teach leadership through past figures, such as the leadership of HR Mohamad Mangoendiproejo. How to take HR Mohamad Mangoendiproejo's leadership values as lessons for millennials in history subjects at SMA Negeri 1 Terbanggi Besar for the 2021/2022 Academic Year. The paper of this study uses a descriptive qualitative research method with a case study approach. In this history subject with the Resident Leadership Values material of Mohamad Mangoendiprojo, students are expected to be able to take several things that can be used as examples of leadership traits and can be practiced in everyday life, such as courage, assertiveness, and nurturing.